The Influence of Mobile Application Quality, Brand Consistency, and Service Reliability on the Digital Customer Experience of Food Delivery Application Users - Rio Haribowo; Flora Grace Putrianti; Ricky Rizkie; Widyatmoko Widyatmoko; Pas Mahyu Akhirianto; Pande Gde Bagus Naya Primananda (Journal of Information System, Technology and Engineering, 2026)
The objective of this study is to analyze the influence of Mobile Application Quality, Brand Consistency, and Service Reliability on Digital Customer Experience Users of food delivery app. Multiple linear regression was used to analyze data collected through online questionnaires. Prior to hypothesis testing, the validity test, reliability test, and classical assumption test were used for the data. The study showed that the Mobile Application Quality, Brand Consistency, and Service Reliability variables had a positive and significant influence on Digital Customer Experience both partially and simultaneously. The coefficient of determination suggests that three independent variables in this research explain the Digital Customer Experience. According to the research findings, application quality, brand consistency, and service reliability shape the digital customer experience in food delivery services. In addition to providing recommendations for food delivery service providers on how to improve their service quality and product competitiveness through effective customer experience management, the study also makes theoretical contributions to digital marketing, customer experience, and digital service management literatures.